UPAYA GURU PEMBIMBING DALAM MENANGANI MASALAH DISIPLIN PESERTA DIDIK DI SMP NEGERI 23 PADANG - Aughnini, Aughnini; Kasih, Fitria (Bimbingan dan Konseling, 2013)
Problem of this research aims to describe the Attempts of teachers Counselor handle Discipline problems at SMP Negeri 23 Padang, purpose of the study is 1). Describing of the Attempts of teachers Counselor handle minor Discipline problems students at SMP Negeri 23 Padang. 2) Describing of the Attempts of teachers Counselor handle moderateÂ Discipline problems students at SMP Negeri 23 Padang and 3). Describing of the Attempts of teachers Counselor handle hard Discipline problems students at SMP Negeri 23 Padang.The type of this research is classified as descriptive research. The study population is all students of SMP Negeri 23 Padang. This research used stratified random sampling. After obtained it results was found 88 samples. Data analysis used the percentage formula. Results of research conducted can be described as follows: 1) Attempts teacher counselor in handling minor disciplinary problems of students included in both categories with a percentage of 67%.2). Attempts teacher counselor in handling moderate disciplinary problems of students included in both categories with a percentage of 68%.3) Attempts teacher counselor in handling hard disciplinary problems of students included in both categories with a percentage of 63%. From this Researchers hope that further enhance the students discipline in the school environment and teachers seeking guidance counselor also helped learners particular discipline often problematic either problem in the category of mild, moderate or hard.